Foreplay-roleplay the effects of gender roles and socio-cultural factors in the decision-making and negotiation process of sexually active young couples - Borje, Danielle Francesca Astrid Lonzanida 1990- (2012)
"This study aims to identify how young couples (ages 15-24) communicate their gender roles in their sexual relationships and how socio-cultural factors affect their decision-making and negotiation process in dealing with sex and other related issues. A purely qualitative research was done by the researchers wherein in-depth interviews of 10 sexually active young couples who live in Metro Manila and 2 sex and culture experts from the University of the Philippines, Diliman were done. Due to the sensitivity of the topic, the researchers interviewed couples close to them to ensure full disclosure and confidentiality. The results were then analysed through descriptive and comparative analysis. Guided by Baxter's Theory of Relationship, Bateson, et al.'s Relational Patterns of Interaction and concepts from the Field of Forces framework formulated by Dr. Lourdes M. Portus, it was found out that although there are still common notions and standards that are imbibed in young individuals by different agencies close to the them, adolescents no longer conform to the roles set by the society. Gender roles are fluid and both males and females are neither dominant nor submissive. However, the study showed that females are now initiators of sexual activities and males tend to submit to their female partners' whims to keep the relationship intact: disregarding the supposed to be macho image of males in a patriarchal society. Socio-cultural factors are ever-present in sexual relationships; family and peers with sexual experience are the most influential social agencies to young adolescent couples. Education inform but does not necessaruly emphasize the feelings and emotional aspect of sex as a biological activity; religion delays PMS and serves as a reminder to young adolescents; mass media especially new media is unfiltered in the Philippines and may contain sexually-explicit content which may trigger ideas of early PMS. Given these influences, it is still the adolescents involved in the sexual relationship who get to decide on whether to conform or not. It is more of a matter of personal beliefs and choices they learn and acquire as they age."